Genetic premarital examination - Benhachani, Zouhir; Djerada, Lakhdar (The International tax journal, 2025)
Genetic diseases and congenital malformations constitute a high percentage of newborns, and it is statistically expected that one in every 25 children will suffer from either a hereditary disease, a severe congenital defect, or a mental retardation resulting from a defect In the genes, some of those afflicted with these diseases die early or need to remain in Hospitalization for a long time or repeatedly, which leads to many economic and psychological problems that affect the patient, the family and society. Practical applications of genetics in humans include genetic counseling and premarital medical examination, as they are two very important procedures in this era and achieve a number of benefits, the most important of which is reducing the spread of hereditary diseases Providing accurate and modern examinations, providing early diagnosis and spreading health awareness to prevent these diseases. Providing advice before marriage, before and during pregnancy, after childbirth, and after diagnosing the condition, and supporting the affected family and providing physical, social, and economic relief.